Psychological impact of social isolation in students of a Public University of Lima - Livia Segovia, José Hector (2021)
The Covid-19 pandemic is generating a great psychological impact on university students and the general population, with the family being an important social support element. The objective of this study was to characterize the psychological impact of social isolation in students of a Public University in Lima. The study employed anon-probabilistic sample of 3,960 students, between 16 and 40 years old, where 40.2%were men and 59.8% women. The Scales of Positive and Negative Emotions (PANAS) and Family Functionality-APGAR were applied. The results indicate that the psychological impact was reflected through positive emotions (alert, interested and attentive) and negative emotions (scared, upset and uneasy). It was also found that the family functioning in the context of confinement reflected that the evaluated shared the problems of the house, as well as spending time in the family. Finally, the correlation of family functioning with negative emotions was r= -.279 and with positive emotions was r= .321. It is concluded that university students have experienced emotions as a result of social isolation, in which having the f68mily as support is an important factor in situations of psychological impact, having to strengthen the orientation and regulation for negative emotions and pay attention to develop positive emotions.